High Nuclear Expression of HDGF Correlates with Disease Progression and Poor Prognosis in Human Endometrial Carcinoma. (17th February 2014) - Wang, Lijing; Jiang, Qingping; Hua, Shengni; Zhao, Mengyang; Wu, Qiangyun; Fu, Qiaofen; Fang, Weiyi; Guo, Suiqun
Abstract : Aims . This study examined the correlation between high nuclear expression of hepatoma-derived growth factor (HDGF) and clinicopathologic data in endometrial carcinoma (EC), including patient survival. Methods . One hundred and twenty-two endometrial carcinoma (EC) patients from 2002 to 2008 were reviewed in the study. HDGF expression in tumor tissues was examined using immunohistochemistry (IHC), and its association with clinicopathological parameters was evaluated. Tumors with 80% or more nuclei staining were regarded as high expression and tumors with less than 80% nuclei staining considered as low expression. Results and Conclusions . Immunohistochemical analysis revealed that HDGF was expressed in both the nucleus and cytoplasm. High nuclear expression of HDGF was positively correlated with FIGO stage (P = 0.032 ), but not associated with other clinical features, such as histological grading or lymph node status. Patients with high expression of HDGF had poorer overall survival rates than those with low expression of HDGF (P = 0.001 ). However, multivariate analyses showed that high nuclear expression of HDGF protein was not an independent predictor of prognosis for EC patients (P = 0.111 ). Our results suggest that high nuclear expression of HDGF is a potential unfavorable factor for the progression and prognosis of EC.